The comparison of dexmedetomidine, esmolol, and combination of dexmedetomidine with esmolol for attenuation of sympathomimetic response to laryngoscopy and intubation in patients undergoing coronary artery bypass grafting - Dipali Singh; Sathyanarayan Jagannath; Shio Priye; A Syed Mudassar (Annals of Cardiac Anaesthesia, 2019)
Background: The aim of this study was to compare the effects of dexmedetomidine, esmolol, and combination of both on control of sympathetic response to laryngoscopy and tracheal intubation in coronary artery disease patients. Material and Methods: A prospective, randomized, double-blinded clinical study included 90 patients scheduled for elective coronary artery bypass surgery. Patients were randomly allocated into three groups of 30 each: dexmedetomidine group (Group D) 1 μg/kg, esmolol group (Group E) 2 mg/kg, and group dexmedetomidine with esmolol (Group DE) 0.5 μg/kg of dexmedetomidine with 1 mg/kg of esmolol. Each drug was diluted with 0.9% normal saline to 20 ml volume and infused in 10 min before induction of anesthesia. Hemodynamic changes (heart rate [HR], arterial blood pressure, and pulmonary artery pressure) were compared at various time intervals as follows-baseline, after study drug, after induction, and 1, 3, and 5 min after intubation. Statistical analysis included analysis of variance, Chi-square, and Fisher's exact test. Results: In Group DE, there was no significant increase in HR at all-time intervals, and the HR was stable compared to Group D and Group E. Blood pressure values were comparable in all groups except in Group E at 5 min. The pulmonary arterial pressures were statistically less in DE group except at 3 and 5 min. Conclusions: The combination of dexmedetomidine and esmolol group has beneficial effect on HR and pulmonary arterial pressures but has no additional advantage with respect to arterial blood pressure when compared with dexmedetomidine and esmolol groups in patients undergoing elective coronary artery bypass grafting.